Design, Synthesis, Characterization, Biological Activity and ADME Study of New 5-arylidene-4-Thiazolidinones Derivatives Having - Duha E. Taha; Ayad M.R Raauf; Karima F. Ali (College of Pharmacy / Mustansiriyah University, 2019)
New series of Nabumetone containing 5-arylidene-4-thiazolidinones pharmacophore as in compounds 3(a-e) were designed and synthesized by using nabumetone and hydrazinethiocarboamide to synthesize compound (1) (Schiff base), next step    compound (1) will react with chloroacetic acid and anhydrous sodium acetate in order to synthesize compound (2) containing 4-thiazolidinone ring this compound will react with 4-benzaldehyde derivatives in the presence of basic media such as piperidine to form compounds 3(a-e). The structures of new intermediate and final synthesized compounds were detected by determination of physical properties (melting points). The structure of synthesized compounds has been confirmed by FT-IR spectroscopy, proton nuclear magnetic resonance (1H-NMR) spectroscopy and carbon 13 nuclear magnetic resonance (13C-NMR) spectroscopy the final synthesized compounds were also screened for their antibacterial and antifungal activity.